Evaluation of a cross-border field simulation exercise on the response to outbreaks of infectious diseases in Namanga, Kenya and Tanzania. - John Sackey Dzaba; Hilary Kagume Njenge; James Wakhungu; Ralf Reintjes; Nicola Watt (Public Library of Science (PLoS), 2024)
Travel and trade, whilst playing a critical role in economic development, contribute to the spread of infectious diseases, including novel or emerging diseases, which can threaten health security locally, regionally and globally. The World Health Organization mandates preparedness through field simulation exercises to address infectious disease outbreaks, as highlighted by the COVID-19 pandemic. This study assessed the impact of the 2019 Namanga field simulation exercise, conducted in the border town shared by Kenya and Tanzania, on improving cross-border outbreak preparedness and response. It focused on participants' knowledge, skills acquisition and real-world application. An anonymous online survey was administered to participants 37 months post-field simulation exercise. In addition, key informant interviews and a focus group discussion with the Joint Border Management Committee in Namanga were conducted. The June 2019 field simulation exercise enhanced the skills, knowledge, and confidence of participants, including members of the border community, in preparing for and responding to outbreaks including COVID-19. The skills and knowledge gained were deemed valuable, relevant, and effective for use in future response activities. The analysis is limited by potential response bias, as only participants with positive experiences of the field simulation exercise may have responded more favourably. Addressing the limitations of design and implementation of the field simulation exercise and the challenges of cross-border response identified in this study are critical to optimising future responses.